Bayesian quantile regression - Tony Lancaster; Sung Jae Jun (Brown University, Department of Economics, 2005)
Recent work by Schennach(2005) has opened the way to a Bayesian treatment of quantile regression. Her method, called Bayesian exponentially tilted empirical likelihood (BETEL), provides a likelihood for data y subject only to a set of m moment conditions of the form Eg(y, ) = 0 where is a k dimensional parameter of interest and k may be smaller, equal to or larger than m. The method may be thought of as construction of a likelihood supported on the n data points that is minimally informative, in the sense of maximum entropy, subject to the moment conditions. Specifically the probabilities pi attached to the n data points are chosen to solve
Keywords: 330; Bayes-Statistik; Regression; Theorie